Three-dimensional printing assisted ORIF versus conventional ORIF for tibial plateau fractures: A systematic review and meta-analysis. (September 2018) - Xie, Linzhen; Chen, Chunhui; Zhang, Yingying; Zheng, Wenhao; Chen, Hua; Cai, Leyi
Abstract: Purpose: The objective of this meta-analysis was to assess the influence of three dimensional printing technology on the open reduction and internal fixation (ORIF) of tibial plateau fractures from current randomized controlled trials and prospective comparative studies. Methods: The electronic literature database of Pubmed, Embase, and Cochrane library were searched in January 2018. The data operation time, intraoperative blood loss, follow-up knee function (Rasmussen score, HSS) and complications (including infection, screw loosening, knee stiffness, knee instability, posttraumatic osteoarthritis, VTE) were extracted. Stata 12.0 software was used for our meta-analysis. Results: 11 RCTs and 6 prospective comparative studies met our inclusion criteria with 358 tibial plateau fractures patients in the 3D group and 378 patients in the routine ORIF group. The meta-analysis showed that there were significant differences in operation time, intraoperative blood loss and bony union time between the 3D group and conventional group. As for the complications and follow-up function recovery evaluated by the excellent and good rate based on HSS and Rasmussen score, no significant differences were found. Conclusion: The 3D group showed shorter operation time, less intraoperative blood loss and faster union time for patients with tibial plateau fractures. Therefore, compared with conventional ORIF, ORIF assisted by three-dimensional printing technology should be a more appropriate treatment of tibial plateau fractures. Further large-sample randomized controlled trials are needed in the future to confirm the superiority of three-dimensional printing assisted ORIF. Highlights: We firstly investigate the evidence of ORIF versus 3D Printing assisted ORIF in treatment of tibial plateau fractures from current RCT and prospective literature. The meta-analysis includes prospective comparative studies and RCT. We found that ORIF with 3D printing might be superior to routine ORIF with shorter operation time, less intraoperative blood loss and shorter time of bony union.